1991
DOI: 10.1128/aac.35.7.1343
|View full text |Cite
|
Sign up to set email alerts
|

Influence of beta-lactamase inhibitors on the potency of their companion drug with organisms possessing class I enzymes

Abstract: The ability of ,-lactamase inhibitors to induce class I W-lactamases in certain organisms in vitro suggests a potential for antagonism in vivo. Therefore, a study was designed to assess the ability of sulbactam and clavulanate to induce P-lactamases in two strains each of Enterobacter cloacae, Citrobacterfreundii, Serratia marcescens, and Pseudomonas aeruginosa both in vitro and in vivo. Induction in vitro was observed only with S. marcescens and P. aeruginosa and generally only when inhibitor concentrations g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

1993
1993
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
(40 reference statements)
0
2
1
Order By: Relevance
“…The antagonism observed between clavulanate and ticarcillin in this study contradicts what has been observed clinically or in animal models of infection (4,15). This discrepancy most likely relates to the presence or absence of host defenses.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…The antagonism observed between clavulanate and ticarcillin in this study contradicts what has been observed clinically or in animal models of infection (4,15). This discrepancy most likely relates to the presence or absence of host defenses.…”
Section: Discussioncontrasting
confidence: 68%
“…However, for ticarcillin-clavulanate, the ability of clavulanate to induce expression of the P. aeruginosa AmpC cephalosporinase (8,20,22) could antagonize the antibacterial activity of ticarcillin in the combination. In immunocompetent mice and humans infected with P. aeruginosa, antagonism between clavulanate and ticarcillin has not been observed (4,15). However, the potential for antagonism in the absence of ade-quate host defenses, i.e., neutropenic patients, has not been systematically studied.…”
mentioning
confidence: 99%
“…To date, the optimal dosing and utilization of ␤-lactamase-inhibitor-␤-lactam combinations have not been extensively studied. Cavalieri et al previously reported that the sequential dosing of sulbactam prior to cefoperazone and ticarcillin in mice enhanced the activities of these combinations against some strains of Enterobacter cloacae and Serratia marcescens producing inducible group 1 ␤-lactamases (5). This increase in efficacy was seen despite the fact that group 1 ␤-lactamases are the least susceptible of all ␤-lactamases to inhibition by sulbactam.…”
mentioning
confidence: 97%